Análise ambiental integrada do componente solo como subsídio para avaliação da sustentabilidade da Bacia Hidrográfica do Rio Tenente Amaral em Jaciara - Mato Grosso - Brasil - Santos, Vanderley Severino dos (2007)
This work has as objective to to apply and compare five different methodologies of environmental analysis and to produce maps thematic that: they characterize the environment, they evaluate the susceptibility and the potential to the laminate erosion, they to determine potential the environmental fragility and emergent, they evaluate the vulnerability to the erosion, esteem the average losses of soil and the production of sediments and thus they evaluate the environmental sustainable of the Water-Basin of the River Tenente Amaral in Jaciara, Mato- Grosso, Brazil. For the present study one uses of techniques of Geoprocessing and cartographic data soil, geology, the geomorphology, the climate, the vegetation and the use of the soil of the region of the Basin, converting them for the digital format. The results demonstrated that the studied area presents high percentage of human activities (84%) predominating the sugarcane cultivation. The soil predominance of type LATOSSOLOS and NEOSSOLOS QUARTZARÊNICOS in soft relief was distinguished in the region proceeding from the claysand layer unconsolidated sediments of the Cochoeirinha Formation that if presents with bigger area of occurrence in the place. With the application of the methodologies for the study of the area it was verified that approximately 55% of it present average the high potential' to the laminate erosion; natural conditions of strong instability `the very strong one'; balance in the occurrence of processes of morphogenese and pedogenese; average losses of high soil had been classified enter `and very high' e, in relation to the production of sediments, was verified that the esteem production more is accented in the places where the use of the soil is intensive, being able to reach up to 0,433 t.ha¹.